What drives Ireland's housing market? A Bayesian DSGE approach - Johannes Gareis; Eric Mayer (University of Würzburg, Department of Economics, 2012)
In this paper we study the drivers of fluctuations in the Irish housing market by developing a dynamic stochastic general equilibrium (DSGE) model of Ireland as a member of the European Monetary Union (EMU). We estimate the model with Bayesian methods using time series for both Ireland and the rest of the EMU for the period from 1997:Q1 to 2008:Q2. We find that housing preference (demand) and technology shocks are the main drivers of fluctuations in house prices and residential investment. Moreover, we find that adding housing collateral does not improve the fit of our model to the data. A standard regression analysis shows that a good part of the variation of housing preference shocks is explained by unmodeled demand factors that have been considered in the empirical literature as important determinants of Irish house prices.
Keywords: E44; E52; F41; 330; housing; monetary policy; Bayesian estimation; Wohnimmobilien; Nachfrage; Schock; Immobilienpreis; Konjunktur; Allgemeines Gleichgewicht; Stochastischer Prozess; Schätzung; Bayes-Statistik; Irland